Optimalisasi Penilaian Kognitif Melalui Media Digital Dalam Pembelajaran Bahasa Indonesia - Ivoni Amelia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article explores the integration of digital media in cognitive assessment in the context of Indonesian language education at the secondary school level. Advances in digital technology enable more adaptive and varied assessment approaches, facilitating efficient evaluation of students' understanding and their ability to apply language concepts. Bloom's revised Taxonomy emphasizes the importance of measuring higher-order thinking skills, which can be enhanced through digital technology to provide students with more rapid and personalized feedback. These findings suggest that the integration of digital technology in cognitive assessment not only increases learning effectiveness but also prepares students to face increasingly complex global educational challenges.